Involvement of SlSTOP1 regulated SlFDH expression in aluminum tolerance by reducing NAD+ to NADH in the tomato root apex. (19th December 2022) - He, Qiyu; Jin, Jianfeng; Li, Pengfei; Zhu, Huihui; Wang, Zhanqi; Fan, Wei; Yang, Jian Li
SUMMARY: Formate dehydrogenase (FDH; EC 1.2.1.2.) has been implicated in plant responses to a variety of stresses, including aluminum (Al) stress in acidic soils. However, the role of this enzyme in Al tolerance is not yet fully understood, and how FDH gene expression is regulated is unknown. Here, we report the identification and functional characterization of the tomato ( Solanum lycopersicum ) SlFDH gene. SlFDH encodes a mitochondria‐localized FDH with K m values of 2.087 mm formate and 29.1 μm NAD + . Al induced the expression of SlFDH in tomato root tips, but other metals did not, as determined by quantitative reverse transcriptase‐polymerase chain reaction. CRISPR/Cas9‐generated SlFDH knockout lines were more sensitive to Al stress and formate than wild‐type plants. Formate failed to induce SlFDH expression in the tomato root apex, but NAD + accumulated in response to Al stress. Co‐expression network analysis and interaction analysis between genomic DNA and transcription factors (TFs) using PlantRegMap identified seven TFs that might regulate SlFDH expression. One of these TFs, SlSTOP1, positively regulated SlFDH expression by directly binding to its promoter, as demonstrated by a dual‐luciferase reporter assay and electrophoretic mobility shift assay. The Al‐induced expression of SlFDH was completely abolished in Slstop1 mutants, indicating that SlSTOP1 is a core regulator of SlFDH expression under Al stress. Taken together, our findings demonstrate that SlFDH plays a role in Al tolerance and reveal the transcriptional regulatory mechanism of SlFDH expression in response to Al stress in tomato. Significance Statement: Formate dehydrogenase (FDH; EC 1.2.1.2.) catalyzes the degradation of formate and the reduction of NAD + to NADH. Here, we demonstrate that the FDH gene SlFDH is induced by aluminum stress in tomato, which relies on the transcription factor SlSTOP1, to enhance tolerance to aluminum stress via SlFDH‐catalyzed reduction of NAD + .